Influencia de los programas de protección y atención al menor implementados por las demunas, en la dinámica familiar de los grupos familiares de los niños y niñas de 8 a 10 años víctimas de maltrato en el distrito de Trujillo, 2000-2001 - Aguilar Paredes, Orealis (2007)
The actual qualitative research of ethnographic character analyzes if DEMUNAS programs are effective in the treatment of cases from children under infantile mistreatment. The problem is analyzed taking in consideration the three actors that participate in this problematic that are the mistreated children. The parents who are generally the ones who mistreated them and the professionals from DEMUNAS who have a participation in treatment of the cases One of the factors that most influence inside the mistreatment children receive is given by the fact that parents have suffered it too. As part of the analysis of this problematic we have to consider that a proposal is realized which spam improvement in the three factors that intervene in the problematic, so what is set out is an integral solution to this situation. The proposal that is set out consider that all the participants of the problem have better ways to avoid this mistreatment, which involves that it is in conditions to have a joint vision of solution and it can, in base to this, improve the treat that children who have been mistreated receive. The conceptual approximation of work is derived from the feelings that express the interviewed and the analysis of contents which are taken out of these, and in base to this information to have right knowledge of what the problems involves and the best way the solution is set out based in the proposal that is set out at the end of research work.